RESPON SELANDIA BARU TERHADA PENDEKATAN TIONGKOK DI OCEANIA TAHUN 2014-2019 - Cattleya Liutantri; Yessi Olivia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research analysed New Zealand’s responses towards China’s geopolitical approach in Oceania particularly in the year of 2014 until 2019. China, who is intensifying its approach to countries in Oceania, is creating political problems for New Zealand. These political problems consist of the disruption of New Zealand’s interests. As a small country, New Zealand has its own strategy in response to China’s approach. New Zealand employs its hedging strategy in the spectrum of economic pragmatism where New Zealand seeks to meet its interests without causing significant damage. This research is conducted by using the descriptive qualitative method with document analysis as its data collecting method. Document analysis is done by evaluating documents such as books, journals, press releases, news, and government publications. This research used the Neorealism perspective and hedging theory. This theory explains countries’ response of hedging toward political problems. This paper showed that, in accordance with the hedging theory, New Zealand's response to its political problem towards China is by maximizing its economic benefits using economic pragmatism strategy. This strategy can be seen from some of New Zealand’s actions such as Joint Statement between New Zealand and the People’s Republic of China on the Establishment of a Comprehensive Strategic Partnership, signing of Belt and Road Initiative’s MoA, and renewal of FTA between China and New Zealand. New Zealand’s actions show its intentions towards continuing its economic relation with China in the future. Therefore, it can be seen that with regard to its political problems with China, New Zealand chooses to defend its economic interests. Keywords: Hedging, Economic Pragmatism, China’s Geopolitical Approach, New Zealand’s Interest.